Effect of Nesting Structure Density on Clutch Success of Canada Geese, Branta canadensis, Nesting in Constructed Wetlands in the Cave Run Lake, Kentucky, Area - Caudill, Teresa L. (Scholarworks @ Morehead State, 1996)
A thesis presented to the faculty of the College of Science and Technology at Morehead State University in partial fulfillment of the requirements for the Degree of Master of Science in Biology by Teresa L. Caudill on November 26, 1996.